The Outcome of Allogeneic Hematopoietic Stem Cell Transplantation From Different Donors in Recipients With Mucopolysaccharidosis - Qu, Yuhua; Liu, Hao; Wei, Likun; Nie, Shushan; Ding, Wenjiao; Liu, Sha; Liu, Haiyan; Jiang, Hua (Frontiers in Pediatrics, 2022)
There is limited information regarding hematopoietic stem cell transplantation (HSCT) for mucopolysaccharidosis (MPS) IV and VI. This study examined the full donor chimerism, specific lysosomal enzyme levels, and the survival of different MPS children after HSCT from various donor sources and compared the prognosis. A total of 42 MPS children underwent HSCT; among them, 9 cases were type I, 14 were type II, 15 were type IV, and four were type VI. 24 patients received peripheral blood stem cells(PBSC), and 18 patients received umbilical cord blood(UCB). 95.2% (40 of 42) of patients achieved full donor chimerism, and all patients' specific lysosomal enzyme levels reached normal. The estimated overall survival (OS) at one year was 92.9%. There was no significant difference in 1-year OS between patients who received PBSC transplantation and those who received UCB grafts (87.5% versus 100%, P = .0247). The incidence of cytomegaloviremia (58.3% and 44.4% respectively in PBSC recipients and UCB recipients) and pneumonitis (45.8% and 33.3%, respectively) was high. However, there were no patients who developed CMV disease, and few patients suffered from respiratory failure (4.2% and 5.6%, respectively) due to pneumonia. All deaths (3 of 42) occurred in patients receiving PBSC grafts, and there was no death in patients receiving UCB grafts. There was no death after transplantation in patients with MPS IV and VI. In addition, respiratory and nervous system functions were improved, whereas valvular heart disease was improved in some patients but progressed in more patients after transplantation. In summary, HSCT is a good therapeutic option for MPS, not only for patients with MPS I or II but also for those with MPS IV or VI. The specific lysosomal enzyme levels of patients can be completely restored to normal, which is the basis for resolving a broad range of clinical outcomes. Moreover, UCB with suitable HLA (HLA-match above 7/10 and 4/6) is a suitable donor source for MPS. Patients receiving UCB transplantation can achieve a higher proportion of full donor chimerism and survival with less severe complications. HSCT can improve organs function in MPS patients, but it is still worth exploring.